TCGA: Increased oncoprotein coding region mutations correlate with a greater expression of apoptosis-effector genes and a positive outcome for stomach adenocarcinoma. Issue 16 (17th August 2016) - Yavorski, John M.; Blanck, George
ABSTRACT: Oncogene mutations are primarily thought to facilitate uncontrolled cell growth. However, overexpression of oncoproteins likely leads to apoptosis in a feed forward mechanism, whereby a certain level of oncoprotein leads to the activation of pro-proliferation effector genes and higher levels lead to activation of pro-apoptotic effector genes. TCGA STAD barcodes having no oncoprotein coding region mutations represented reduced expression of the apoptosis-effector genes compared with barcodes with multiple oncoprotein coding region mutations. Furthermore, STAD barcodes in a "no-subsequent tumor" group, representing 224 samples, and in a "positive outcome" group, had more oncoprotein coding regions mutated, on average, than barcodes of the new tumor and negative outcome groups, respectively. BRAF, CTNNB1, KRAS and MTOR coding region mutations (as a group) had the strongest association with the no-subsequent tumor group. Tumor suppressor coding region mutations were also correlated with no-subsequent tumor. These results are consistent with an oncoprotein-mediated, feed-forward mechanism of apoptosis in patients. Importantly, the no-subsequent tumor group also had more overall mutations. This result leads to considerations of unhealthy cells or cells with more neo-antigens for immune rejection. However, a probabilistic aspect of mutagenesis is also consistent with more oncoprotein and tumor suppressor protein mutations, in cases of more overall mutations, and thus a higher likelihood of activation of feed forward apoptosis pathways.